On some Indo-Pacific boring endolithic Bivalvia species introduced into the Mediterranean Sea with their host – spread of Sphenia rueppelli A. Adams, 1850 - ZENETOS, A.; OVALIS, P.; EVIKER, D. (Mediterranean Marine Science, 2010)
The study of the endolithic molluscs found on/in living alien Spondylusshells collected in the Gulf of Iskenderun (Turkey) brought to light three more alien bivalvia species namely Petricola hemprichi, Gastrochaena cymbium and Sphenia rueppelli. The presence of Sphenia rueppellideserves attention as it constitutes the first record of this species as living in the Mediterranean Sea. The definitive establishment and spreading of these bivalves in the basin seems to be also attested by careful analysis of specimens sampled in other southern Turkish localities and previously retained in local private collections. The present records raise some questions on the vector of arrival of the species in the Mediterranean Sea that could be strictly connected with their hosts.